Marginality: Addressing the root causes of extreme poverty - Franz W. Gatzweiler; Heike Baumüller; Christine Ladenburger; Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2011)
The need to address extreme poverty from the perspective of marginality arises from the frustration that the number of the poorest and hungry remains unacceptably high. This triggered the call for an innovative approach from the side of science and action. The conceptual and analytical framework developed here views marginality as a root cause of extreme poverty. We define marginality as an involuntary position and condition of an individual or group at the edge of social, economic, and ecological systems, preventing the access to resources, assets, services, restraining freedom of choice, preventing the development of capabilities, and causing extreme poverty. Causal complexes tie the marginalized poor in systems from which they want to escape or in which they want to improve their lives. The rural and agricultural context is of particular relevance here, as we assume that large segments of the extreme poor live in rural areas. The poorest themselves have described their situation, for instance, as being trapped in a 'complex knot which can lead to further knots if the wrong threads are pulled.' While poverty is objectively a matter of absolute deficiencies, we explain why the way in which poverty is perceived by the poor themselves requires looking at poverty as a relative, subjective, dynamic and systemic phenomenon. We conceptualize marginality as patterns of causal complexes in societal and spatial dimensions. These causal complexes can, for instance, comprise different types of livelihood systems or different types of poverty traps. They include proximate as well as underlying causes of extreme poverty and specifically address social exclusion, restrained access to assets, opportunities and transport, communication and public services infrastructure. An analytical framework is developed, outlining the various steps required for the analysis of marginality in a systematic, re]iterative and participatory manner, involving those affected by extreme poverty themselves. From each causal complex of marginality, leverage points can be identified which match with specific intervention packages, relevant for livelihood management, policy formulation and implementation. The approach to the investigation of extreme poverty is applied and relevant for managing change towards inclusive development. Points of entry for public and private investments are being identified.
Keywords: 330; Marginality; extreme poverty; complexity; systems; change; interventions